Sepucuk surat dari seorang bangsawan Gowa di tanah pembuangan (Ceylon) - Suryadi, S. (Wacana, Journal of the Humanities of Indonesia, 2008)
This paper looks at an early nineteenth-century Malay letter from a land of exile, Ceylon (present Sri Lanka). The letter, written in Colombo, was dated 3 January 1807 and is in Leiden University Library MS Cod.Or.2241-I 25 [Klt 21/no.526]. It was written by Siti Hapipa, the widow of the exiled Sultan Fakhruddin Abdul Khair al-Mansur Baginda Usman Batara Tangkana Gowa, the 26th king of the Gowa Sultanate of South Sulawesi who reigned from 1753 until 1767. He was banished by the Dutch (Vereenigde Oost-Indische Compagnie, VOC) to Ceylon in 1767 on a charge of conspiracy with the British to oppose the VOC trading monopoly in eastern Indonesia. Although many studies of Malay letters exist, letters from the lands of exile like such as the one discussed in this article have received less scholarly attention. Also remarkable is that this is one of the rare eighteenth- and nineteenth-centuries Malay letters written by a female. Setting the scene with a historical sketch of the eighteenth and the early nineteenth century in colonial Ceylon and the Netherlands East Indies, this paper provides the transliteration of Siti Hapipa's letter in Roman script, through which I then analyse the socio-economic and political aspects of the family of Sultan Fakhruddin in their exile in Colombo.